Assessing Financial Performance as a Mediator in the Corporate Governance-Company Value Relationship: Insights from the IDX Banking Sector - Sahabuddin, Romansyah; Selamanda, Amalia Reviska; Sari, Evi Puspita; Ramli, Muhammad Fajrul; Arif, Hery Maulana (International Humanity Advance, Business & Sciences, 2024)
This study is designed to understand the impact of good corporate governance on firm value with financial performance as an intervening variable with the object of research, namely banking companies in the Indonesia Stock Exchange (IDX) gallery. The population studied was all banking companies listed on the Indonesia Stock Exchange (IDX) gallery for the period 2019 - 2023. The type of research used is quantitative method. The sampling technique used purposive sampling technique and took as many as 7 banking companies that met the requirements to be studied. This research uses PLS (Partial Least Square) which uses the SmartPLS version 4.0 application. The research results obtained show that 1) Good Corporate Governance has a significant effect on firm value, 2) Good corporate governance has a significant effect on financial performance, 3) Financial performance has a significant effect on firm value, 4) Financial performance is able to be intervening between good corporate governance and firm value.